Student Self-Disclosure in the Modern Era: The Role of Group Guidance Services at the Institute Islam Ma’arif Jambi - Rizki Adiyatma; Sri Rahmah Ramadhoni; Teri Santera (KONSELI: Jurnal Bimbingan dan Konseling (E-Journal), 2025)
Group guidance services are often used and used as a means to improve individual skills because in this service there are group dynamics. Individuals are expected to be more open or active in expressing their opinions, because self-disclosure is one of the principles of group guidance services. This study aims to describe how self-disclosure of students of the Ma'arif Islamic Institute Jambi in participating in group guidance services is seen from five aspects of self-disclosure, namely, accuracy, motivation, conditions, intensity, depth and breadth. The subjects in this study were all students of the Ma'arif Islamic Institute Jambi who had participated in group guidance services activities in the 2024/2025 academic year, totaling 43 students. The data collection technique in this study was carried out using a Likert scale model developed regarding self-disclosure, which in total consists of 42 items. The data of this study were analyzed using descriptive analysis statistical techniques used to see the picture of student self-disclosure in participating in group guidance services. The research findings prove that the self-disclosure of students of the Ma'arif Islamic Institute Jambi when carrying out group guidance services as a whole is in the moderate category, namely 53.49%. The implications of this research for guidance and counseling are that counselors can describe what aspects exist in an individual's self-disclosure.